To solve the equation "x - 6 = 12," you would add 6 to both sides of the equation to isolate the variable. This gives you x = 18 as your final answer. This is because adding 6 to both sides cancels out the -6 on the left side, leaving you with x = 12 + 6, which simplifies to x = 18.
-12 minus -6 is -6
Oh, that's a happy little math problem you've got there! To write the sentence "18-6-6-6 equals 0," you simply subtract each number from left to right. So, 18 minus 6 is 12, 12 minus 6 is 6, and 6 minus 6 is 0. Just like painting a beautiful landscape, take it step by step and you'll reach the perfect answer!
2(2*4-5)+6 = 12
12.
6 divided by 11 minus 1 divided by 2 equals?
6 - -12 = 18
6
66
The expression "12 minus 6 divide 3" simplifies to "12 - (6 รท 3)". The division 6 รท 3 equals 2, so the expression simplifies further to "12 - 2". Finally, the subtraction 12 - 2 equals 10. Therefore, the answer to 12 minus 6 divide 3 is 10.
rainbows I dont think its that.
6
6
7-1=6 6+6=12
-6 - (-8) = 2
19 minus 6 equals 13. This subtraction operation involves taking away 6 from 19, resulting in a difference of 13. In mathematical terms, this can be represented as 19 - 6 = 13.
-6 when you multiply two minus numbers the minus signs cancel each other out so -12 * -6 = 72
-12 minus -6 is -6